THEORETICAL ASPECTS OF THE ROLE OF THE SHADOW ECONOMY - Zarina, Liga; Zvaigzne, Anda; Klodane, Aļona (Journal of Regional Economic and Social Development, 2022)
The shadow economy is definitely a significant problem throughout the world. Research studies on the shadow economy still lack a single approach to the term shadow economy. Several definitions of the shadow economy are used to assess the role of the shadow economy.The present research aims to examine the theoretical role of the shadow economy and the definitions thereof given in various economic theories.Analysing the definitions of the shadow economy, researchers identify ambiguous interpretations of the term given in various theories. The term shadow economy has a considerable number of synonyms used for researching the shadow economy. Some definitions focus on hidden outcomes, whereas others focus on hidden employment. A definition of the shadow economy is of great importance in assessing the size of the shadow economy.The research employed the following methods: monographic, descriptive, as well as analysis, synthesis and document analysis.